The Role of CD44 in the Pathophysiology of Chronic Lymphocytic Leukemia - Gutjahr, Julia Christine; Greil, Richard; Hartmann, Tanja Nicole (Frontiers in Immunology, 2015)
CD44 interactions with hyaluronan (HA) play a key role in various malignancies, supporting tumor cell migration, adhesion, and survival. In contrast to solid tumors, the expression of CD44 standard and variant forms and their functional interplay with hyaluronan is less understood in hematological malignancies. Chronic lymphocytic leukemia (CLL) is a highly abundant B cell malignancy with a well coordinated balance between cell cycle-arrest and proliferation of tumor subpopulations. The long-term survival and proliferation of CLL cells requires their dynamic interactions with stromal and immune cells in lymphoid organs. Interactions of HA with CD44 and HA-mediated motility receptor (RHAMM) contribute to CLL cell localization, and hence CLL pathophysiology, by shaping homing, interstitial migration, and adhesion of the tumor cells. CD44 can complex with key prognostic factors of CLL, particularly CD38 and CD49d, bridging the gap between prognosis and cellular function. Here, we review the current evidence for the individual and associated contributions of CD44 to CLL pathophysiology, the dynamic functional regulation of CD44 upon CLL cell activation, and possible therapeutic strategies targeting CD44 in CLL.